Risk Factors For Stunting In Toddlers - Henrico Tampatianus Bago; Imelda F.E Manurung; Indriati Andolita Tedju Hinga (Universitas Nusa Cendana, 2022)
This study aims to analyze several risk factors for stunting in children under five that are rarely studied in Indonesia and the Province of East Nusa Tenggara, namely factors of water, hygiene, environmental sanitation, history of the quantity of maternal ANC visits during pregnancy, and family food security. This research was conducted in the working area of ​​the Noemuti Health Center. This research is an analytic observational study with a case-control study approach and consists of a case sample of 36 toddlers and a control sample of 36 toddlers. Data analysis in this research is a bivariate analysis using the chi-square test. The results of the analysis show that eight variables are risk factors for stunting in toddlers in the work area of ​​the Noemuti Health Center in 2021, namely birth distance, family food security, adequacy of clean water, clean water sources, physical quality of clean water, mother's hand washing habits with soap and running water, history of quantity of maternal antenatal care visits during pregnancy, and frequency of illness. Health promotion efforts and cross-sectoral cooperation are needed to tackle the stunting problem.